METHODICAL SYSTEM OF SKILLED WORKERS PROFESSIONAL TRAINING IN THE CONDITIONS OF BLENDED LEARNING (Innovative professional education, 2023)
The article is devoted to the description of the structure of the methodical system skilled workers professional training in the conditions of blended training. The content of the methodological-targeted, substantive, procedural-organizational and control-regulatory components of the specified system is revealed.
Keywords: professional education, professional training of skilled workers, blended learning, distance learning, methodical system